Rehabilitasi peninggian dimensi vertikal oklusi pada kasus kehilangan gigi sebagian dengan atrisi - Wirahadikusumah , Andy (Fakultas Kedokteran Gigi Universitas Trisakti, 2023)
Background: In this modern era, patients are increasingly critical of perfect results, we as dentists are required to work systematically. Correct centric and eccentric occlusion relationships are very important in the construction of removable dentures. Errors at the stage of determining jaw relations, especially the vertical dimensions, can cause the artificial teeth to be uncomfortable for the patient to use or have the long-term potential to damage elements of the stomatognathic system. Objective: In this case report, it is hoped that we can distinguish which cases require an increase in the vertical dimension and which do not, as well as knowing how to carry out the procedure for increasing the vertical dimension in cases where the teeth have experienced attrition resulting in a decrease in the vertical dimension. Case: A patient who had experienced attrition of the lower anterior teeth and was exacerbated by loss of the upper anterior teeth, resulting in a decrease in the vertical dimension. Case management: Rehabilitation to increase the vertical dimension was carried out first using an interim acrylic partial denture and enameloplasty of the lower anterior teeth. After the patient adapts, a metal frame partial denture is made as a definitive denture and a fixed denture on the remaining natural teeth to maintain the vertical dimensions that have been obtained. Conclusion: The key to success in this case is an accurate and systematic treatment plan, with an increase in the vertical dimension, as well as good communication with the patient.